Design of an Enhanced Temperature Control System for Neonatal Incubator - Tisa, Tamanna Afrin; Nisha, Zinat Ara; Kiber, Md Adnan (Bangladesh Journal of Medical Physics, 2013)
Worldwide every year over 4 million infants die within a month of birth. Of this number, 3.9 million belong to the developing world. Some (25%) of this deaths are caused due to complications of prematurity, most often due to improper heat regulation, water loss and neonatal jaundice. An infant incubator provides stable levels of temperature, relative humidity and oxygen concentration. Temperature control system is the most important part of a baby incubator which has to be maintained around 37°C. In the present work we have designed and developed an enhanced temperature control system incorporating a combination of Pulse Width Modulation (PWM) and simple ON-OFF control system, where thermistors have been used as temperature sensors. The range of variation of temperature against the set temperature (37°C) has been found to be 1°C which is satisfactory. A temperature monitor has been designed through a circuit network incorporating a thermistor so that the voltage output is linearly related to the temperature. This allowed the use of a simple millivoltmeter to display the temperature directly through appropriate scaling. To ensure the safety of the baby an alarm circuit was designed which provides sound alarms for personnel attention if the temperature goes beyond a specified safe range, chosen here as 26°C 38°C. In developing countries, like Bangladesh frequent power cuts demand an uninterrupted operation of incubator and a battery back up system, which could also be powered by a solar panel, has been suggested for this purpose. DOI: http://dx.doi.org/10.3329/bjmp.v5i1.14668 Bangladesh Journal of Medical Physics Vol.5 No.1 2012 53-61